The Natural Pavilion: Circular, Bio-based, Remountable, Inspiration-pavilion - DP6 (Firm) (urbanNext, 2023)
Green Solution House 2.0 is a hotel in the town of Rønne on the Danish island of Bornholm. Developed in very close collaboration between 3XN and GXN, the hotel s design is rooted in rigorous sustainability principles with regard to materials, construction, and performance, and it is an uncompromising development of the adjoining Green Solution House completed by 3XN and GXN in 2015.
DP6, Energy and sustainability, Middle Density, Project, Technology and fabrication, Urban Paradigms.
Adaptive reuse, Almere, Architecture&climate, Architecture&environment, Assembly, Biodiversity, Biomaterial, Circular design, CO2 emissions, Comfort, Flexibility, Greenery, Optimized construction, Pavilion, Project, Rain Water Harvesting, Raw materials, Sustainable, The Netherlands, Timber Structure, Well-being, Wood construction.
Keywords: Technology and fabrication; Middle density; Energy and sustainability; urban paradigms; Adaptive reuse; CO2 emissions; Almere, Netherlands; Netherlands